Tolerance and potential for adaptation of a Baltic Sea rockweed under predicted climate change conditions - Luca Rugiu; Iita Manninen; Eva Rothäusler; Veijo Jormalainen (Elsevier Ltd, 2022)
Climate change is threating species' persistence worldwide. To predict species responses to climate change we
need information not just on their environmental tolerance but also on its adaptive potential. We tested how the
foundation species of rocky littoral habitats, Fucus vesiculosus, responds to combined hyposalinity and warming
projected to the Baltic Sea by 2070–2099. We quantified responses of replicated populations originating from the
entrance, central, and marginal Baltic regions. Using replicated individuals, we tested for the presence of withinpopulation
tolerance variation. Future conditions hampered growth and survival of the central and marginal
populations whereas the entrance populations fared well. Further, both the among- and within-population
variation in responses to climate change indicated existence of genetic variation in tolerance. Such standing
genetic variation provides the raw material necessary for adaptation to a changing environment, which may
eventually ensure the persistence of the species in the inner Baltic Sea.